ANALISIS PENGELOLAAN ANGGARAN DANA DESA DI KECAMATAN LOHIA KABUPATEN MUNA - Kasmanderi, Kasmanderi; Syaifuddin, Dedy Takdir; Amstrong, Valentinus; Zaluddin, Zaluddin; Madi, Riski Amalia (Jurnal Manajemen dan Kewirausahaan, 2024)
The aim of this study; (1) To find out what the village government does in managing village funds;(2) Tofind out the factors that influence the management of village funds. The population in this study was thevillage government of Lohia District. This research uses interview, observation and documentation methods. The research results show that; Village fund management in Lohia District, Muna Regency is effective and in accordance with Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Fund Management.